2009
DOI: 10.1177/1545109709332019
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Cushing's Syndrome in HIV-Infected Patients Receiving Ritonavir and Inhaled Fluticasone: Description of 4 New Cases and Review of the Literature

Abstract: Protease inhibitors boosted with ritonavir can lead to drug-drug interactions, particularly with inhaled corticosteroids such as fluticasone, because of the potent inhibition of cytochrome P450-3A4 activity. We report 4 cases of iatrogenic Cushing's syndrome after concomitant administration of inhaled fluticasone and antiretroviral therapy including a protease inhibitor boosted with ritonavir. Although typical manifestations were present, diagnosis of Cushing's syndrome was delayed because the patients were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…The interaction between inhaled/intranasal Fluticasone and the potent Protease inhibitor, Ritonavir, in HIV infected patients are well documented causing Iatrogenic Cushing syndrome by the mention mechanism. Two series of systematic reviews were shown those effects in both adult and children [38,39]. The combination median time of treatment was 4 months and the duration for symptom correction was 3.6 months [40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between inhaled/intranasal Fluticasone and the potent Protease inhibitor, Ritonavir, in HIV infected patients are well documented causing Iatrogenic Cushing syndrome by the mention mechanism. Two series of systematic reviews were shown those effects in both adult and children [38,39]. The combination median time of treatment was 4 months and the duration for symptom correction was 3.6 months [40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…This has been reported elsewhere3 11 12 and, though the exact mechanism is not well-understood, the prolonged hyperglucocorticoid state is believed to activate T-lymphocyte apoptosis.…”
Section: Discussionmentioning
confidence: 69%
“…Current antiretroviral regimens often contain the HIV protease inhibitor ritonavir, and co-administration with topical fl uticasone results in a dramatic increase in the latter bioavailability. This may result in iatrogenic Cushing's syndrome as alerted in increasing number of case reports (Mahlab-Guri et al 2011 ;Kedem et al 2010 ;Valin et al 2009 ;Samaras et al 2005 ). Ironically, in patients treated by ritonavir, older generations of topical glucocorticoids appear to be safer options (Foisy et al 2008 ).…”
Section: General Treatment Of Allergic Rhinitismentioning
confidence: 96%